Pathology and Protein Changes of the Spinal Dural Arteriovenous Fistula Arterial Draining Vein Under Sustained High Vascular Pressure - Liu, Peixi; Shi, Yuan; Li, Sichen; Liu, Yingjun; Zhou, Yingjie; Song, Yaying; Zhu, Wei; An, Qingzhu (Frontiers in Neurology, 2021)
Object: Spinal dural arteriovenous fistula (SDAVF) is the most common spinal vascular shunt lesion. Although pathological changes in the SDAVF draining vein (SDAVF-DV) have been elucidated, protein changes remain enigmatic. We investigated the pathology and protein changes in the SDAVF-DV under sustained high vascular pressure. Methods: Three SDAVF-DV samples were compared with superficial temporal artery (STA) and superficial temporal vein (STV) samples as controls. Vascular structure was revealed by hematoxylin and eosin (H&E) and Masson staining; and cell distribution, extracellular matrix, and inflammation infiltration were observed by immunohistochemistry. Label-free quantitative proteomics was performed, and the peptide mixture was fractionated and analyzed by liquid chromatography–tandem mass spectrometry (LC-MS/MS) to identify differentially expressed proteins. Bioinformatics analysis of the differentially expressed proteins was performed using Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and protein–protein interaction (PPI) networks. Results: H&E and Masson staining showed an artery-like structure of the SDAVF-DV. Immunostaining showed that vWF+ cells were not continuous in the SDAVF-DV. Although α-SMA+ and AT1+ cells were more abundant in the STV than in the SDAVF-DV, piezo-1 expression was lower in the SDAVF-DV. The SDAVF-DV showed different distributions of elastin, COL I, and COL III. COL IV and COL VI were decreased in the SDAVF-DV, while CD45+ cells and COX-1 were increased compared with those in the controls. No differences in CD68 expression and COX-2 staining were observed between the SDAVF-DV and controls. Compared with the STA, 95 proteins were upregulated and 303 proteins were downregulated in the SDAVF-DV. The most differential GO terms in each category were the adenylate cyclase-modulating G protein-coupled receptor signaling pathway, U6 snRNP, and SH3 domain binding. The most differentially expressed KEGG protein pathway was focal adhesion. Compared with the STV, the SDAVF-DV had 158 upregulated proteins and 362 downregulated proteins. The most differential GO terms in each category were lamellipodium assembly, U6 snRNP, and SH3 domain binding; and the most differentially expressed KEGG protein pathway was dilated cardiomyopathy. PPI analysis revealed PPIs among the top 300 proteins. Conclusions: The SDAVF-DV exhibits specific pathology and protein expression changes under sustained high vascular pressure. The results of the present study provide insights into the pathogenesis of SDAVF formation at the protein level as well as a scientific foundation for further exploration of the pathophysiological mechanism of the SDAVF.